RNA-labelled Ro and La ribonucleoprotein complexes reassembled in vitro; characterization by gel shift analysis - GRANGER, D (Blackwell Science Inc, 1996)
Ro and La RNP complexes were reassembled from in vitro labelled hY5 RNA and HeLa cell extracts. These complexes were then visualized through retardation of migration of labelled hY5 RNA in non-denaturing polyacrylamide gels. Three major complexes (named A, B, and C) were formed when crude cellular extracts (S100 fraction) were used. Using monospecific anti-60-kD Ro (Ro60) and anti-La antibodies to retard RNPs containing these antigens during migration in the gels, the three major complexes were shown to contain Ro60 (C), La (B), or both proteins (A). The specificity of RNA–protein interactions in the reassembled complexes was further demonstrated using two 3′-shortened hY5 RNA transcripts lacking the La-binding site (hY5–Alu I RNA) and both the Ro60 and La-binding sites (hY5–Hha I RNA). hY5–Hha I RNA still formed a single, minor complex when incubated with S100 extract, suggesting interaction with a yet undefined protein. In addition, we used the capacity of specific antibodies to retard the migration of the ressembled complexes to design a detection assay for anti-Ro and anti-La autoantibodies. Using 84 human sera, our assay was shown to approximate the specificity and sensitivity of an immunoprecipitation assay where (32)P-labelled cell extracts are used as source of antigens. Our assay may be used to detect low levels of antibodies to conformational determinants on Ro60 and La proteins in human sera and antibody preparations.